THE EVOLUTION OF THE LEGAL FRAMEWORK FOR THE ESTABLISHMENT AND MANAGEMENT OF STATE-OWNED ENTERPRISES IN INDONESIA: A COMPREHENSIVE LITERATURE REVIEW ON REGULATORY HARMONISATION, THE ROLE OF THE STATE AS A SHAREHOLDER, AND IMPLICATIONS FOR MODERN CORPORATE GOVERNANCE - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The evolution of the legal framework for the establishment and management of State-Owned Enterprises (SOEs) in Indonesia has undergone a significant transformation from the pre-reform era public law paradigm to a modern corporate model through Law No. 19 of 2003, which was revised by Law No. 1 of 2025. with this comprehensive literature review focusing on sectoral regulatory harmonisation, the role of the state as a controlling shareholder through the Daya Anagata Nusantara Investment Management Agency (BPI Danantara), and the implications for corporate governance based on international Good Corporate Governance (GCG). Harmonisation was achieved through the separation of SOE assets from the state budget under Article 4B and operational holdings under Government Regulation No. 15 of 2025, while the role of the state evolved into professional stewardship with the strengthening of the Business Judgment Rule (BJR) in Article 9F, which protects the autonomy of the board of directors, the independence of 50% external commissioners, and the transfer of auditing to public accountants to increase operational efficiency and global competitiveness. This normative legal study concludes that the reconstruction of these norms supports the optimal contribution of SOEs to the national economy towards Indonesia Emas 2045, with recommendations from the National GCG Centre and regulatory digital synergy.